Synthesis and Electrochemical Evaluation of MSNs-PbAE Nanocontainers for the Controlled Release of Caffeine as a Corrosion Inhibitor - Martín Aguirre-Pulido; Jorge A. González-Sánchez; Luis R. Dzib-Pérez; Montserrat Soria-Castro; Alejandro Ávila-Ortega; William A. Talavera-Pech (MDPI AG, 2022)
In this paper, a controlled-release system of caffeine as a corrosion inhibitor was obtained by encapsulating it in MCM-41 silica nanoparticles coated with a poly(β-amino ester) (PbAE), a pH-sensible polymer. Encapsulation was verified using Fourier transform infrared spectroscopy (FTIR) and thermogravimetry (TGA). The release of caffeine from the nanocontainers was analyzed in electrolytes with pH values of 4, 5, and 7 using UV-Vis, showing a 21% higher release in acidic electrolytes than in neutral electrolytes, corroborating its pH sensitivity. Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization were used to determine the inhibition mode and efficiency of the encapsulated and free caffeine. The caffeine released from the nanocontainers showed the highest efficiency, which was 85.19%. These results indicate that these nanocontainers could have potential use in smart anticorrosion coating applications.